PEMBENTUKAN KARAKTER DEMOKRATIS PESERTA DIDIK DI SMA AL AZHAR SURABAYA - Muhammad Ali; Listyaningsih (Universitas Negeri Surabaya (Unesa), 2025)
Abstract This research aims to describe the process of forming democratic character at Al Azhar High School based on democratic principles, including: freedom, equality, brotherhood and participation. This type of research is qualitative with descriptive methods. The theory used in this research is Thomas Lickona's character education theory. The focus of this research is on the process of forming democratic character with four main principles. Data collection techniques use semi-structured interviews, observation and documentation. The data analysis procedure goes through the stages of data collection, data reduction, data presentation, and conclusions. The results of the research show that the formation of democratic character runs according to democratic principles and the process is carried out in the classroom and in the dormitory. The school carries out good habits in accordance with democratic principles in every activity in the classroom and in the dormitory, one of which is freedom in the formation of class equipment and randomization of levels between classes in dormitory rooms, with the aim of forming a democratic character in students. The smooth running of various activities in the school and dormitory is carried out in accordance with democratic principles. Keywords: formation, democratic character, class and dormitory